Effects of sedatives on diaphragm activity monitored by ultrasound: a systematic review and meta-analysis - Jiaren Luo; Luhao Wang; Bilin Wei; Zhikun Huang; Huifang Zheng; Bin Gu; Fei Pei; Zenan Chang; Yang Liu; Xiangdong Guan; Xuyu Zhang; Zimeng Liu (BMC Anesthesiology)
Abstract Background Current research lacks comprehensive evaluations on the inhibitory effects of sedatives on diaphragm activity under ultrasound monitoring. This meta-analysis aims to launch this problem by systematically analyzing the available evidence. Methods The EMBASE, PubMed, and Web of Science databases were searched. Original studies that explored the effects of sedative agents on human diaphragm activity via ultrasound were eligible. The quality of the included studies was evaluated using the Revised Cochrane Risk-of-Bias tool for randomized trials (RoB 2) and the Newcastle–Ottawa Scale (NOS). The pooled assessment encompassed alterations in diaphragmatic motion (DM) and diaphragmatic thickening fraction (DTF). Mean difference (MD) with 95% confidence intervals (CI) were calculated. The trial sequential analysis (TSA) was performed to calculate the required information size (RIS). The strength of evidence was assessed using the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) Pro Guideline Development Tool (GDT). Subgroup analysis and meta-regression was conducted to explore heterogeneity. Sensitivity analysis was used to evaluate the robustness for the meta-analysis results. Results Six randomized controlled trials and four prospective observational studies involving 727 patients were ultimately included. In the pooled analysis, DM and DTF were measured at three time points: during sedation (T1), upon awakening (T2), and at baseline (T0). Comparisons were conducted between the values at each time point, revealing mean differences (MDs) for DM of 2.54 mm (95% CI [2.01, 3.08], P < 0.00001, I2 = 92%) (T0 vs. T1), − 1.14 mm (95% CI [-1.90, -0.93], P < 0.00001, I2 = 95%) (T1 vs. T2), and 1.47 mm (95% CI [ 0.90, 2.05], P < 0.00001, I2 = 92%) (T0 vs. T2). For DTF, the corresponding MDs were 0.11 (95% CI [0.09, 0.13], P < 0.00001, I2 = 89%), − 0.06 (95% CI [− 0.08, − 0.04], P < 0.00001, I2 = 88%), and 0.04 (95% CI [0.03, 0.05], P < 0.00001, I2 = 71%). Subgroup analyses further demonstrated that the MDs at T0 vs. T1 for DM and DTF were 3.62 mm (95% CI [3.15, 4.10], P < 0.00001, I2 = 76%) and 0.13 (95% CI [0.11, 0.14], P < 0.00001, I2 = 75%), respectively, in the propofol group, compared to 1.65 mm (95% CI [1.21, 2.09], P < 0.00001, I2 = 73%) (DM) and 0.09 (95% CI [0.08, 0.10], P < 0.00001, I2 = 0%) (DTF) in the group receiving propofol in combination with other sedatives. Sensitivity analysis suggested high robustness of the analysis for DTF. The TSA indicated that the sample size was sufficient. And GDT showed a low but important strength of this review. Conclusion This meta-analysis reveals that sedatives can inhibit diaphragm activity, with this negative impact persisting post-awakening. Propofol alone achieves a more pronounced reduction in diaphragm activity than when combined with other sedatives. However, significant heterogeneity remains across studies due to data limitations and low evidence certainty. Further research is crucial to establish evidence-based recommendations for optimal diaphragm-protective sedation strategies. Trial registration The protocol was registered at the PROSPERO international prospective register of systematic reviews (CRD42024514504).